Perancangan Sistem Informasi Pemesanan Ruang Rapat Dan Konsumsi Di Bagian Umum Sub. Rumah Tangga Universitas Sebelas Maret Surakarta - tasmin - tasmin; Chairullah - Naury; Kresno Ario Tri Wibowo (Politeknik Harapan Bangsa Surakarta, 2022)
The process of borrowing meeting rooms currently running in the General Section of the Sub-Household of Sebelas Maret University Surakarta (UNS) is done manually. The meeting committee met with the General Section of the UNS Sub-Household to order a meeting room and its consumption. Then the Admin of the General Section of the UNS Sub-Household saw the record data in the room reservation book in advance to inform which room could be used for meetings. To speed up and simplify the process of borrowing a meeting room, it is necessary to design a meeting room reservation information system. Based on the description of the background, it can be formulated that the problem to be solved in this research is